Phosphatidylinositol‐4, 5‐bisphosphate is enriched in granulovacuolar degeneration bodies and neurofibrillary tangles. Issue 4 (June 2014) - Nishikawa, Tomokazu; Takahashi, Tetsuya; Nakamori, Masahiro; Yamazaki, Yu; Kurashige, Takashi; Nagano, Yoshito; Nishida, Yoshihiko; Izumi, Yuishin; Matsumoto, Masayasu
<x xml:space="preserve">Abstract</x> Aims Among the pathological findings in Alzheimer's disease (AD), the temporal and spatial profiles of granulovacuolar degeneration (GVD) bodies are characteristic in that they seem to be related to those of neurofibrillary tangles (NFTs), suggesting a common mechanism underlying the pathogenesis of these structures. Flotillin‐1, a marker of lipid rafts, accumulates in lysosomes of tangle‐bearing neurones in AD patients. In addition, recent reports have shown that GVD bodies accumulate at the nexus of the autophagic and endocytic pathways. The aim of this study was to elucidate the distribution of the lipid component of lipid rafts, phosphatidylinositol‐4, 5‐bisphosphate [PtdIns(4, 5)P2], in AD and other neurodegenerative disorders. Methods We compared PtdIns(4, 5)P2 immunoreactivity in the hippocampus, entorhinal cortex and neocortex of five AD cases, 17 cases of other neurodegenerative disorders and four controls. In addition, we performed double staining using markers of GVD, NFTs and lipid rafts for further characterization. Results Immunohistochemical analysis revealed that PtdIns(4, 5)P2 was selectively enriched in GVD bodies and NFTs. Although immunoreactivity for PtdIns(4, 5)P2 was also evident in NFTs composed of hyperphosphorylated tau, PtdIns(4, 5)P2 was segregated from phosphorylated tau within NFTs by double immunofluorescence staining. In contrast, PtdIns(4, 5)P2 colocalized with the lipid raft markers flotillin‐1 and annexin 2, within GVD bodies and NFTs. Conclusions These results suggest that lipid raft components including PtdIns(4, 5)P2 play a role in the formation of both GVD bodies and NFTs.